Flexibility of the "rigid" classics or rugged bottom of the folding funnels of myoglobin, lysozyme, RNase A, chymotrypsin, cytochrome c, and carboxypeptidase A1. (1st January 2017) - Uversky, Vladimir N.
ABSTRACT: The abilities to crystalize of a globular protein and to solve its crystal structure seem to represent triumph of the lock-and-key model of protein functionality, where the presence of unique 3D structure resembling aperiodic crystal is considered as a prerequisite for a given protein to possess specific biologic activity. The history of protein crystallography has its roots in first crystal structures of myoglobin, lysozyme, RNase A, chymotrypsin, cytochrome c, and carboxypeptidase A1 solved more than 50 y ago. This article briefly considers extensive structural information currently available for these proteins and shows that the bottoms of their folding funnels (i.e., the lowest parts of their potential energy landscapes) are not smoothed but rugged. In other words, these crystallization classics are characterized by significant conformational flexibility and are not rigid (immobile) crystal-like entities.